Supporting early design decision making using design context knowledge. (30th October 2007) - Rehman, Fayyaz U.; Yan, Xiu-Tian
The decisions made at conceptual design are crucial to the overall success of a product as they affect all the downstream phases of the product life-cycle, user satisfaction of the product and the environment in which the product is to be used and disposed of. Owing to a lack of availability of knowledge and understanding about the complexity of such knowledge spanning these different life phases, designers find it difficult to foresee the implications or consequences of their decisions made at conceptual design on the product's life-cycle, its users and its operational environment. This paper explores the true meaning of design context knowledge by studying how these pieces of knowledge can be formalised and, more importantly, how they can be used in a structured way to support decision making and the prediction of their consequences at the conceptual design stage. A case study is presented to illustrate the strengths of this approach, followed by formal evaluations of the approach and a prototype system developed in this research.